Badania nad ekonomiką kształcenia w Polsce - Gmytrasiewicz, Michał; Kluczyński, Jan (Wydział Prawa i Administracji UAM, 1971)
In this article the authors discuss the development of investigations on the economy of education in Poland. They present more detailed results of work on such problems as: planning and prognosis in branches of education, financing and costs of education, infrastructure of schooling and economic effectivity of education. In addition the authors in attempting to present the object and range of economy of education drew up the three following groups of problems: a) macroeconomic education on a national economic scale, b) microeconomic problems of education regarding the school system itself, c) individual profitability of education. The authors express their conviction that wider practical application of the results of economic-educational research may lead to increased effectivity of envestments designated, by the community, for education. Increasing this effectivity means that by more rational economy of investments^ and greater effectivity in their utilization a relatively larger number of beitter qualified specialists, of various standards, can be educated.
Investigation on the Economy of Education in Poland